Socialization in Extremist Movements: A Case Study of Al-Qaeda - Gomaa, Omar; Pandian, Sivamurugan; Ahmad Pazil, Nur Hafeeza (Al-Basirah Journal, 2021)
Again, it's still unclear for sociological scholars, how Al-Qaeda socializes its cohorts based on abomination towards the West and the Arab regimes. This research paper focuses on the socialization process within Al-Qaeda through (Family, School, Peers and Media). Also, it argues that not all of those who join Al-Qaeda ostracized by their perspective community, but most of who join Al-Qaeda are well educated and came from a well-to-do family. However, from face to face socialization to hosted sites and social media, Al-Qaeda influenced thousands of its target audience to join the organization in its battle against Western interests. Additionally, Al-Qaeda came up by a new technique of socialization through an online magazine that teaches those who cannot join Al-Qaeda to manufacture bombs at their homes to attack the infidels as Osama Bin Laden says “Al-Qaeda desires death more than your desires live”.